2019
DOI: 10.3390/nu11112753
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Patterns and the Double Burden of Malnutrition in Mexican Adolescents: Results from ENSANUT-2006

Abstract: Mexico is facing the double burden of malnutrition, and adolescents are not an exception. Diet plays an important role, both in causing overweight and undernutrition. This study aimed to describe the dietary patterns (DPs) of Mexican adolescents and to examine its association with nutritional status using data from adolescents aged 12–19 years (n = 7380) from the National Survey of Health and Nutrition (ENSANUT-2006). Principal component analysis was used to derivate the DPs. Associations between DP and nutrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 45 publications
2
14
0
Order By: Relevance
“…In México, western and plant-based dietary patterns were simultaneously associated with a higher prevalence of overweight-obesity and at least one undernutrition indicator (Zarate-Ortiz et al 2019). In the context of the double burden of malnutrition, dietary advice must consider malnutrition in all its forms (Zarate-Ortiz et al 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In México, western and plant-based dietary patterns were simultaneously associated with a higher prevalence of overweight-obesity and at least one undernutrition indicator (Zarate-Ortiz et al 2019). In the context of the double burden of malnutrition, dietary advice must consider malnutrition in all its forms (Zarate-Ortiz et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In México, western and plant-based dietary patterns were simultaneously associated with a higher prevalence of overweight-obesity and at least one undernutrition indicator (Zarate-Ortiz et al 2019). In the context of the double burden of malnutrition, dietary advice must consider malnutrition in all its forms (Zarate-Ortiz et al 2019). Gain in height among boys, but not in girls, in early childhood, was associated with lower adiposity in late childhood compared with children with a slower rate of growth (Barrios et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The coexistence of underweight with both wasting and stunting was reported by two studies (42,43) . Three studies presented the burden of coexistence of micronutrient de ciency with undernutrition (stunting or underweight) or with overweight/obesity (32,35,44) (Table-3).…”
Section: Resultsmentioning
confidence: 99%
“…coexistence of underweight with stunting, coexistence of underweight with wasting, and coexistence of underweight with wasting and stunting both, and they did not nd a signi cant association of coexisting forms of undernutrition with child age (42) . The problems relating to undernutrition appear to diminish with increasing age, while the probability of coexistence of stunting with overweight/obesity or coexistence of overweight/obesity with micronutrient de ciency rises (27,30,36,44,49) . In contrast, Zhang, et al, (2016) reported that every year of increasing age signi cantly reduced the odds of coexistence of stunting with overweight/obesity by 0.74 (95% CI: 0.71 to 0.77) (34) .…”
Section: Contributing Factors Of Coexisting Forms Of Malnutritionmentioning
confidence: 99%
“…The characteristics of the anemia-inflammation-related dietary pattern were similar to those of the Western dietary pattern, including high intakes of meat, processed meat, refined grains, fried foods, and sugary foods [42]. A cross-sectional study showed that the Western pattern was correlated with increased prevalence ratios (PR) of anemia (girls: PR = 1.24, 95% CI 1.06, 1.45) and being overweight/obese (boys and girls: PR = 1.15, 95% CI 1.08, 1.21) in Mexican adolescents aged 12-19 years [43]. Additionally, a previous study performed with Thai girls aged 13-15 years reported that 85.5% students consumed dietary iron at <67% of the Recommended Daily Allowance, and most students ate fewer green vegetables and fruits with their meal and drank more sweetened juice [44].…”
Section: Dietary Pattern and Anemiamentioning
confidence: 99%